Drying characteristics of piper betle linn leaves using vacuum and heat pumps drying methods - Mgt Ahmad, Puteri Farah Wahida (2013)
Piper betle L. belongs to genus Piper of Piperacea family. It is locally called as sirih and betel in English. It is deep green heart shaped of leaves. The vine is dioeciously where male and female plants are different, shade perennial root climber. It has been proved by scientific findings of therapeutic properties in betel leaves that bioactive extract of this plant has significant potential in developing into herbal products. However, lack of literature in processing of this herbal extract found. There are two active phytochemicals found in betel leaves namely hydroxychavicol (HC) and eugenol (EU) which contribute to various beneficial bioactivities. Lab-scale synthesis of these phytochemicals has been reported but the technical information for its mass production is not available. The objectives of this study are to investigate the drying behavior of vacuum drying and heat pump drying of betel leaves on drying kinetics and to evaluate the effects of drying parameters on quality of dried betel leaves. In order to investigate the behavior of betel leaves, vacuum drying was chose to shorten the drying time by lowering the boiling point of water to evaporate at low temperature. Heat pump was chosen due to low relative humidity of the dried air use in heat pump system at low temperature. As for vacuum drying method, temperatures were set at range from 30 to 70˚C and the vacuum pressure of 0, 38, and 76cmHg. The optimum drying condition for vacuum drying process was determined at temperature of 70˚C under vacuum pressure of 76cmHg. The drying kinetics was successfully modeled using Handerson & Pabis model. For heat pump drying of betel leaves, temperatures were set as 30, 35 (ambient), and 39˚C. The results shows drying characteristics values at temperature of 39˚C and was modeled using Page model. The assessment of color for dried betel leaves were found that at vacuum pressure plays insignificant changes to the color of dried betel leaves. Color of dried betel leaves generally dependent on the drying temperature applies. The quality of color of dried betel leaves lost as the temperature increased. Same observation was found for dried betel leaves using heat pump drying method. Phytochemical compounds contained in the dried betel leaves were analyzed using high performance liquid chromatography (HPLC) and found that when using vacuum drying process there was significant loss for both EU and HC. For heat pump drying process, EU and HC loss dependent on the temperature applied during drying process.